Who's on First? Is It Fixation That Drives Sensation? Or Is It Sensation That Controls Fixation? - Hussey, Eric S. (Optometry & Visual Performance, 2019)
Background: Fixation is the pause in saccadic eye movements that allows visual information to be sent to the cortex. Small fixational eye movements support stability of sensation during fixation, but yet to be established is whether stable sensation is required for properly controlled fixational eye movements. Methods and Results: The vision science literature describes the motor side of fixation and how drifts and microsaccades work to keep the visual signal alive; that is, how they work to keep visibility intact. The clinical literature describing intermittent central suppression suggests possible effects on motor accuracy in fixation. Putting the vision science together with the clinical picture may help in understanding some of the problems associated with intermittent central suppression such as reading difficulty. Conclusions: Understanding fixational eye movements allows description of probable eyeaiming errors that could occur during intermittent central suppression and that constitute a "spin-cycle" of aiming errors and sensory defects that interfere with accuracy in vision. The vision science provides the details of the motor and sensory parts of the spin-cycle.